2018
DOI: 10.1051/0004-6361/201732442
|View full text |Cite
|
Sign up to set email alerts
|

The ALMA Frontier Fields Survey

Abstract: Context. Characterizing the number counts of faint (i.e., sub-mJy and especially sub-100 μJy), dusty star-forming galaxies is currently a challenge even for deep, high-resolution observations in the FIR-to-mm regime. They are predicted to account for approximately half of the total extragalactic background light at those wavelengths. Searching for dusty star-forming galaxies behind massive galaxy clusters benefits from strong lensing, enhancing their measured emission while increasing spatial resolution. Deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 93 publications
5
28
0
Order By: Relevance
“…These studies mainly sample the bright end of the 1 mm galaxy population and correspond to a flux density range of > n S 1 mJy. The studies at 1.1-1.3 millimeters correspond to deep fields and large mosaics in blank and lensing fields (Hatsukade et al 2013(Hatsukade et al , 2016Aravena et al 2016;Dunlop et al 2017;Umehata et al 2017;Franco et al 2018;Hatsukade et al 2018;Muñoz Arancibia et al 2018) as well as to the combination of multiple targeted fields (Ono et al 2014;Carniani et al 2015;Fujimoto et al 2016;Oteo et al 2016). Our results are in agreement with the results from other studies at S ν >0.1 mJy but are lower than the rest at fainter flux density values.…”
Section: Number Countssupporting
confidence: 91%
See 1 more Smart Citation
“…These studies mainly sample the bright end of the 1 mm galaxy population and correspond to a flux density range of > n S 1 mJy. The studies at 1.1-1.3 millimeters correspond to deep fields and large mosaics in blank and lensing fields (Hatsukade et al 2013(Hatsukade et al , 2016Aravena et al 2016;Dunlop et al 2017;Umehata et al 2017;Franco et al 2018;Hatsukade et al 2018;Muñoz Arancibia et al 2018) as well as to the combination of multiple targeted fields (Ono et al 2014;Carniani et al 2015;Fujimoto et al 2016;Oteo et al 2016). Our results are in agreement with the results from other studies at S ν >0.1 mJy but are lower than the rest at fainter flux density values.…”
Section: Number Countssupporting
confidence: 91%
“…The next step was to conduct deep ALMA surveys to search for the population of faint DSFGs. These first attempts focused on fields with deep archival data such as the Subaru/ XMM-Newton Deep Survey Field (Hatsukade et al 2013(Hatsukade et al , 2016, SSA22 (Umehata et al 2017), the GOODS-S/Hubble Ultra Deep Field (HUDF, Aravena et al 2016;Walter et al 2016;Dunlop et al 2017;Franco et al 2018;Hatsukade et al 2018), Frontier Fields (González-López et al 2017;Muñoz Arancibia et al 2018), on calibrator fields (Oteo et al 2016), and on combined multiple single-pointing fields (Ono et al 2014;Carniani et al 2015;Fujimoto et al 2016;Oteo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hatsukade et al 2013;Ono et al 2014;Carniani et al 2015;Oteo et al 2016;Fujimoto et al 2016), or source numbers found in lensing cluster fields (e.g. González-López et al 2016;Muñoz Arancibia et al 2018), we estimate an expected 1.2-mm source density of 0.6-2 × 10 3 deg −2 , where the lower estimate (from Oteo et al 2016) is derived from a relatively large area of different fields used for the serendipitous searches, which might be expected to reach beyond the effects of cosmic variance. Thus, the number of sources we find in the ALMA pointings of G073.4−57.5 is a factor of 8-30 higher than estimates of the average number of mm sources in the sky.…”
Section: Source Countsmentioning
confidence: 99%
“…The pace of progress of our understanding of the nature and properties of the SMG population has accelerated in the last five years, owing to the commissioning of the Atacama Large Millimetre/Submillimetre Telescope (ALMA), which has enabled high-sensitivity ( 1 mJy rms) and highangular-resolution ( 1 FWHM) observations in the sub-/millimetre wavebands of samples of dust-obscured galaxies at high redshifts, including SMGs. In the first few years of operations, ALMA has been used to undertake a number of typically deeper continuum surveys of small contiguous fields (including lensing clusters and proto-cluster regions), with areas of 10s of arcmin 2 (Walter et al 2016;Hatsukade et al 2016;Dunlop et al 2017;Umehata et al 2018;Hatsukade et al 2018;Franco et al 2018;Muñoz Arancibia et al 2018). These small field studies typically contain modest numbers of sources at flux limits of S 870 0.1-1 mJy (corresponding to star-formation rates of ∼ 10-100 M yr −1 ) and so provide a valuable link between the bright SMGs seen in the panoramic single-dish surveys and the populations of typically less-actively star-forming galaxies studied in UV/optical-selected surveys.…”
Section: Introductionmentioning
confidence: 99%